Application of 360° Virtual Reality Technology (VR360 Virtual Tour) in Life Skills Education for 5-6-year-old Preschool Children - Hong Nhung, Chu Thi; Trang, Tran Thi Huyen (VNU Journal of Science: Education Research; Vol 42 No 2DO - 10.25073/2588-1159/vnuer.5319, 2026)
This paper presents the results of a study on the application of 360° virtual reality technology (VR360 Virtual Tour) in life skills education for 5–6-year-old preschool children. Based on the national preschool education curriculum and research on innovative, technology-integrated teaching methods, the authors propose a VR360 model aimed at enhancing visualization, experiential learning, and interaction in life skills instruction. The research employed a mixed-methods approach, including document analysis; surveys of 50 teachers and 50 parents; in-depth interviews with 6 teachers, 3 school administrators, and 5 parents; and a pedagogical experiment involving 30 children. The experimental content focused on designing 15 lessons across five core skill groups, utilizing 360° videos integrated with interactive hotspots. Data were collected through checklists, behavioral observations, and post-lesson feedback. Findings indicate that VR360 increased children's engagement, self-service abilities, communication, problem-solving, and creative thinking. Over 90% of teachers and 100% of experts assessed the model as feasible and effective. The study proposes a competency framework for life skills education and offers recommendations on infrastructure investment, teacher training, and the development of age-appropriate digital learning resources for 5-6-year-olds.